Manfaat Digitalisasi Sebagai Media Promosi Dan Publikasi Untuk Mengembangkan Kesenian Di Desa Jenisgelaran, Jombang - Novi Andari; Sudarwati; Sarindat, Evalyn Suryanti (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
The existence of art must continue to be maintained as a form of regional identity and as national wealth which must be preserved and recognized by the Indonesian people themselves and so that it is not stolen by other countries. In this digital era, existence through the digitalization process is absolutely necessary so that it can be spread widely and easily. Several programs launched in the DRTPM Community Service Grant for the 2023 implementation year in Jenisgelaran Village, Bareng District, Jombang Regency are implemented using counseling and training methods, including counseling on the benefits of digitalization for promotion and publication, online media management training, and training on creating promotional video content and publications given to maintain and develop the existence of art groups in this village in the form of online promotions and publications. The activity was attended by participants who were targeted, namely village officials, artists and youth organizations. The activity produced positive results, shown by the presence of participants exceeding the target number, where the target number was 25 people, but approximately 30 people attended. Based on the questionnaire distributed, it can be stated that most of the participants who attended had skills regarding digital technology, but were still not optimal, so these three activities were provided so that village communities with full awareness and independence promote and publish the potential of their local culture to a wide audience through the use of digitalization.